Detecção de impactos em estruturas unidimensionais utilizando o método TDOA (Time Difference of Arrival) - Garcia, Gabriella Faina (Universidade Federal de São Carlos, 2018)
Impact is a dynamic load on a structure in which a high module force is applied within a short period of time. Then, as the impact has affected a steel beam, it is possible to analyze the mechanical signals measured produced by the piezoelectric sensors. Therefore, in this thesis, the Time Difference of Arrival (TDOA) method is used to detect the impact. It consists of utilizing two sensors placed within a known distance from each other, which have the objective of localizing the impact through measures of the wave transmitted along the beam by the dynamic load. The localization of the impact was done using the method in question and then compared to its actual position.
Impact detection in unidimensional structures using TDOA (Time Difference of Arrival)
Keywords: Detecção de impacto; TDOA; Sensores piezoelétricos; Impact detection; Piezoelectric sensors; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS